Migration and population origin of Negotin municipality at the beginning of the 20th century - Apanović Zlatko (Zbornik Radova: Geografski Fakultet Univerziteta u Beogradu, 2019)
The area of the municipality of Negotin, which belonged to the historically important area of Krajina, represented the polygon of intersection of migration flows of different intensity and directions. Studying the origins of the population enables us to understand the currently ethnic division of settlements created by the migrations and ethnic processes that influence the settlements which are the subject of this paper. This article aims to describe the migration flows that determined the origin of the population of the municipality of Negotin and the ethnic distribution of settlements. The results of anthropogeographic surveys conducted during the second and third decades of the 20th century, as well as ethnological research from the second half of the 20th century, can rightly be interpreted as supporting the claim that the origin of the population and the ethnic structure of settlements of the municipality of Negotin are largely the result of historical migration trends. Of the greatest importance for the ethnic distribution of population are its two migration flows. The first and the oldest migration flow from Kosovo and Metohija and stage areas for that migrant lineages (families who have a mutual ancestor) and the second and the most numerous migration flow is from Wallachia, in which the participating lineages of Serbian and Vlach origin which created conditions for further deepening of the differences between Serbian and Vlach settlements.